"A Sealed Rectilinear Planet": The Skyscraper as Vertical Heterot opia in J. G. Ballard's High-Rise and Ben Wheatley's Screen Adaptation. Issue 4 (November 2020) - Klein, Sascha
This article addresses the role of vertical detachment in J. G. Ballard's novel High-Rise (1975/2006) and its recent screen adaptation by Ben Wheatley (2015) through the lens of Michel Foucault's concept of heterotopia (1967/1984). In particular, it elucidates the specific pressures and possibilities of high-rise living by drawing on Foucault's distinction between heterotopias of compensation and illusion as well as by assessing their roles in the residents' gradual slide into tribal anarchy, as charted by the novel and the film. Throughout, my findings are embedded in the context of modern architecture and urban planning, most notably high-rise housing, in postwar Britain and its reflection in other influential cultural productions of the time. Finally, the idea of heterotopia is championed as central to Ballard's continual engagement with a 'dark logic' inherent in modern architecture and technology. The article thus contributes to ongoing debates on verticality and height as factors in past and current urbanistic schemes and their social and psychological impact as reflected in professional discourses as well as in literary-artistic engagements (see "vertical turn" in Graham & Hewitt, 2013).